Antiviral and anti-inflammatory activities of pochonin d, a heat shock protein 90 inhibitor, against rhinovirus infection - Song, Jae Hyoung; Shim, Aeri; Kim, Yeon Jeong; Ahn, Jae Hee; Kwon, Bo Eun; Pham, Thuy Trang; Lee, Jongkook; Chang, Sun Young; Ko, Hyun Jeong (Biomolecules and Therapeutics, 2018)
Human rhinoviruses (HRV) are one of the major causes of common cold in humans and are also associated with acute asthma and bronchial illness. Heat-shock protein 90 (Hsp90), a molecular chaperone, is an important host factor for the replication of single-strand RNA viruses. In the current study, we examined the effect of the Hsp90 inhibitor pochonin D, in vitro and in vivo, using a murine model of human rhinovirus type 1B (HRV1B) infection. Our data suggested that Hsp90 inhibition significantly reduced the inflammatory cytokine production and lung damage caused by HRV1B infection. The viral titer was significantly lowered in HRV1B-infected lungs and in Hela cells upon treatment with pochonin D. Infiltration of innate immune cells including granulocytes and monocytes was also reduced in the bronchoalveolar lavage (BAL) by pochonin D treatment after HRV1B infection. Histological analysis of the lung and respiratory tract showed that pochonin D protected the mice from HRV1B infection. Collectively, our results suggest that the Hsp90 inhibitor, pochonin D, could be an attractive antiviral therapeutic for treating HRV infection.
Keywords: Anti-inflammatory; Antiviral activity; Heat-shock protein 90; Pochonin D; Rrhinovirus